Kajian Literatur : Problem Solving Seorang Pendidik dalam Menghadapi Tantangan Metode Pembelajaran Diskusi di Kelas pada Mata Pelajaran Bahasa Indonesia - Faizatul Khoiriyah; Miftahul Jennah; Mulyadi Bagas Wicaksono; Agus Milu Susetyo (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This research aims to identify challenges and solutions in implementing discussion learning methods in Indonesian language subjects. Through a literature review, it was found that the main challenges lie in low student participation, teachers' lack of ability to manage discussions, and limited time and resources. Apart from that, the heterogeneity of students' abilities is also an obstacle. To overcome these challenges, this research presents several solutions, including: creating a conducive learning environment, providing space for exploration for students, improving teacher skills, motivating students, and improving classroom management. By implementing these solutions in an integrated manner, it is hoped that discussion learning can become more effective and achieve the desired learning goals. This research concludes that the successful implementation of the discussion method is very dependent on the joint efforts of various parties, including teachers, students and schools. Thus, discussion learning can be an effective means for developing students' language, critical thinking and collaboration skills.